2021
DOI: 10.2217/cer-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of GP40021 insulin lispro biphasic compared with Humalog Mix 25 in Type 2 diabetes mellitus patients

Abstract: Aim: To compare safety (immunogenicity) and efficacy of a biosimilar insulin GP-Lis25 and a reference insulin Ly-Lis25 (Humalog Mix 25) in Type 2 diabetes mellitus (T2D) patients. Materials & methods: This randomized open-label, 26-week clinical trial enrolled 210 T2D patients, randomized 1:1 to twice-daily GP-Lis25 or Ly-Lis25. The primary end point was immune response at 26th week. Noninferiority margin for HbA1c was 0.4%. Results: Immune response frequency was similar in GP-Lis25 and Ly-Lis25 groups bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition, the safety results of Yamada et al and our study in hypoglycemia and severe hypoglycemia are 0.99 (95% CI 0.96 to 1.03) versus 0.96 (95% CI 0.85 to 1.09) and 1.09 (95% CI 0.80 to 1.47) versus 1.06 (95% CI 0.85 to 1.31), respectively. This study includes newly RCTs [ 25 , 28 30 ], pooled more comprehensive evidence in both long−/short acting insulin biologics, reports consistent outcomes than the previous study. However, our study grouped the studies with corrections combined with hypoglycemic drugs, and the results of the study were found to be similar (change of HbA1C at weeks 26, the MD were 0.03; 95% CI − 0.02 to 0.07, p = 0.28).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, the safety results of Yamada et al and our study in hypoglycemia and severe hypoglycemia are 0.99 (95% CI 0.96 to 1.03) versus 0.96 (95% CI 0.85 to 1.09) and 1.09 (95% CI 0.80 to 1.47) versus 1.06 (95% CI 0.85 to 1.31), respectively. This study includes newly RCTs [ 25 , 28 30 ], pooled more comprehensive evidence in both long−/short acting insulin biologics, reports consistent outcomes than the previous study. However, our study grouped the studies with corrections combined with hypoglycemic drugs, and the results of the study were found to be similar (change of HbA1C at weeks 26, the MD were 0.03; 95% CI − 0.02 to 0.07, p = 0.28).…”
Section: Discussionmentioning
confidence: 85%
“…A total of 196 records were screened and 89 full-text articles were assessed for eligibility. Fourteen articles were selected for qualitative review [ 17 30 ]. The trial selection procedure is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tested drugs would be investigated on diabetes mellitus populations throughout the immunogenicity investigation similarly to previously developed rapid-acting insulin biosimilars. [14][15][16] Insulin glulisine was measured by mathematical correction of total insulin, evaluated by nonspecific ELISA. Corrections were made by Owen's method used in clamp studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although healthy subjects are not a target population for insulin glulisine treatment, it does not impact the biosimilarity investigation. Tested drugs would be investigated on diabetes mellitus populations throughout the immunogenicity investigation similarly to previously developed rapid‐acting insulin biosimilars 14–16 …”
Section: Discussionmentioning
confidence: 99%